Strategic Planning Technology Validity Turing Tests Using Artificial Intelligence Understanding - Wan Ahmad, Wan Fatimah; Saputra, Yogi (JESII: Journal of Elektronik Sistem InformasI, 2024)
Turing test has been used as an artificial intelligence (AI) countermeasure for decades. This test measures a machine's capacity for intelligent behavior that is comparable to human capacity. However, Turing's trial has come under fire due to its emphasis on linguistic behavior and potential anthropological bias. The primary goal of this study was to determine whether the Turing Test's validity was connected with comprehension and disclosure of artificial intelligence's aim. The Likert scale was utilized for data gathering, statistical analysis using linear regression, and theoretical analysis. Both qualitative and quantitative research approaches will be used in this investigation. Reviews of the literature and conversations with authorities on the Turing Test and artificial intelligence will be used to gather qualitative data. This resulted in significant advancements in our knowledge of the variables influencing the Turing Test's validity, particularly with regard to comprehending and illuminating the function of artificial intelligence. It is anticipated that this research will yield a technical planning method that will help numerous fields and increase the validity of the Turing Test. This strategy will be grounded in the most recent knowledge about the operation of AI.